Yes or No for Mobile Banking Apps: An empirical Investigation of adoption Factors - Chopra, Sheena; Sharma, Dr. Rasna (The journal of contemporary issues in business and government, 2021)
In this era of Clouds, Banking services have stepped into the new world. From traditional Branch base banking services to Modern online banking Services which include internet Banking, Mobile banking Apps etc. With the emergence of Modern Services there seems a gap between services delivered and adoption by the people. So it is important for the service providers to analyze the gap. This paper tries to examine factors influencing adoption of Mobile Banking Apps. A total of 145 respondents examined through convenient sampling. Through the demographic analysis it is observed that a typical mobile banking user is young literate, female students The Findings further suggest that factors like Social Influence, timeeffectiveness, Simplicity and usefulness acts a major factors that influence the decision for adoption of Mobile banking Apps .Thus , these Factors help service providers to understand the youth intention and to make strategies accordingly to provides maximum inclusion and helps in achieving the mission of Digital India .